2010
DOI: 10.3945/jn.109.120717
|View full text |Cite
|
Sign up to set email alerts
|

Red Meat and a Fortified Manufactured Toddler Milk Drink Increase Dietary Zinc Intakes without Affecting Zinc Status of New Zealand Toddlers1–4

Abstract: Evidence suggests that New Zealand (NZ) children are mildly zinc deficient and may respond to dietary change. A 20-wk randomized intervention trial was therefore conducted to determine whether an increased intake of red meat or consumption of a fortified manufactured toddler milk drink (FTMD, fortified with zinc and other micronutrients) would increase dietary zinc intakes and improve the biochemical zinc status of 12- to 20-mo-old NZ toddlers. Toddlers were randomized to a red meat intervention (n = 90), FTMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…The results of our study support the limited research that shows no evidence that consumption of foods fortified with Fe has a negative effect on Zn absorption (30,32) or Zn status (32,33) in young children. The absorption of Zn from the study formulae was similar to that previously reported in infants (36) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of our study support the limited research that shows no evidence that consumption of foods fortified with Fe has a negative effect on Zn absorption (30,32) or Zn status (32,33) in young children. The absorption of Zn from the study formulae was similar to that previously reported in infants (36) .…”
Section: Discussionsupporting
confidence: 80%
“…Whether Fe supplements given alone compromise infant Zn nutrition is still unclear (21,(27)(28)(29) . When present as a fortificant, Fe does not appear to inhibit Zn absorption (30)(31)(32) , impair Zn status (32)(33)(34) or result in measurable circulating non-transferrin-bound Fe (16) . Few studies, however, have addressed this in infants.…”
mentioning
confidence: 99%
“…A total of 34 studies were identified that reported outcomes on children [36-38,43,46,47,50,61-64],[67-69,71-76,82,86,87,92,93,98],[102,105,115,117,118,121,122,130]. Three of these were before-after studies and the rest were RCTs and quasi-experimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Such relations may be apparent in older age groups because they consume larger portions of flesh foods compared with young children. However, even in meatbased randomized controlled trials in young children, no positive response in serum zinc has been reported (40,41).…”
Section: Assessment Of Zinc Statusmentioning
confidence: 96%
“…The substitution of cow milk with these fortified milk drinks is likely to be an acceptable practice for young children following lactoovovegetarian diets, because it does not require any behavior change, can be used concurrently with breastfeeding, and could increase their intakes of iron and zinc substantially, given the large amounts of milk often consumed (23,82). Moreover, the consumption of fortified toddler milks has produced positive impacts on anemia rates and biomarkers of iron (83-85) but not zinc (41,83) status. Evidence for improvements in functional health outcomes such as growth, morbidity, and cognitive function from the consumption of milk and cereal foods cofortified with zinc and iron is, however, inconclusive on the basis of a systematic review (81); more long-term studies examining these functional health outcomes are required.…”
Section: Dietary Practices To Enhance the Adequacy Of Iron And Zinc Imentioning
confidence: 97%